Instagrammable Tourism: Analisis Dampak Visualisasi Destinasi di Era Media Sosial - Wahyu Wibowo; Ahmad Choiri; Nur Azizah Panggabean; Nur Fatiha; Nur Rahmi irfaniah (Yayasan Literasi Sains Indonesia, 2025)
The development of social media, especially Instagram, has driven a paradigm shift in global tourism practices, from physical experiences to digitally curated visual experiences. One manifestation of this change is the emergence of the phenomenon of Instagrammable tourism, a tourism trend based on visual aesthetics that encourages tourists to choose destinations not only because of cultural or natural values, but also because of their shareable visual appeal. This study aims to systematically and critically examine the literature that discusses destination visualization in the context of social media, especially Instagram, with a focus on the construction of meaning, aesthetic curation, and its implications for tourist behavior and destination branding strategies. Using a literature study approach, this article identifies six main themes: the conceptualization of Instagrammable tourism, visual representation of destinations, digital aesthetics and visual culture, the influence of content on tourist intentions and loyalty, social media-based branding strategies, and the ethical and ecological impacts of visual dominance. The results of the study show that destination visualization not only shapes tourist perceptions but also forms new norms in tourism consumption and space production. On the other hand, excessive aestheticization also presents serious challenges such as the overcommodification of local culture, loss of authenticity, and ecological pressures due to digital overtourism. This study suggests the need for a sustainable, contextual and ethical visual approach in social media-based tourism development.